The Role of Emotions in the Life of the Individual - Happiness: Array - Mocanu, Lacramioara (New Trends in Psychology, 2021)
In human beings, the experience of an emotion usually involves a set of perceptions, attitudes and beliefs about the world, which we use to assess a particular situation and thus influence how the situation is perceived. Emotion is the affective state we experience, a subjective reaction to the environment that is accompanied by organic changes (physiological and endocrine) of an innate origin, influenced by experience. Emotions have a function of adapting our body to everything that surrounds us. Emotions, being affective states, indicate personal internal states, motivations, desires, needs and even goals. In any case, it is difficult to say how the emotion will affect the future behavior of the individual, although it may help adaptare, cogniție, us to know him intuitively.